Interactions between HCl, NO(x), and H2O ice in the Antarctic stratosphere - Implications for ozone - Wofsy, S. C.; Salawitch, R. J.; Fox, L. E.; Mcelroy, M. B.; Molina, M. J. (1988)
The role of PSC particles in determining the distributions of HCl and chlorine radicals is studied. The thermodynamics of HCl in ice is discussed, showing that significant quantities of HCl may be dissolved in ice when PSCs form. It is argued that HCl and HNO3 will be removed from the gas phase early in the condensation process, when only small quantities of H2O have been condensed, reflecting the thermodynamic properties of the solid phases of HCl, HNO3, and H2O. Rapid heterogeneous chemical reactions then volatilize reactive chlorine gases and convert NO(x) to solid-phase nitrates, which can be removed by gravitational settling. Analysis of the suite of heterogeneous chemical processes in the polar stratosphere implies a threshold for HCl concentrations, above which chemical loss rates for ozone increase dramatically.